DETERMINATION OF SOME HEAVY METALS RESIDUES IN RAW MILK OF COWS , SHEEP AND GOATS IN Al-QADISIYA GOVERNORATE - & Ali, Taher (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This study was carried out in Al-Qadisiya Governorate during the period from December , 2012 to March , 2013. Involving five regions with different geographical locations (Diwania city center , Saniya District , Shafeia District, Daghara District and Al-Hamza District ) to determine the residues of nickel , arsenic and mercury in raw milk of cows , sheep and goats . A total of 150 raw milk samples were collected from 150 animals belong to the three species, involved 50 samples for cows, 50 samples for sheep and 50 samples for goats (10 samples / region) selected randomly. Atomic absorption spectrophotometry was used to determine the concentration of nickel (NI) , arsenic (AS) and mercury (Hg) . The results showed that a significant differences (p<0.05) in the concentrations of nickel , arsenic and mercury among milk of cows , sheep and goats . Sheep milk had a higher concentration of nickel 0.563mg / l , arsenic 0.283 mg / l and mercury 0.124 mg / L-1 and lower concentration pattern of these metal in cow’s milk ( 0.221 , 0.122 and 0.037 mg / L-1) respectively . The results also revealed a significant differences (p<0.05) among studied regions . The higher concentrations of these metal were in Al-Hamza District for nickel 0.494 mg / L-1 ,for arsenic 0.246 mg / L-1 and for mercury 0.119 mg / L-1 . While the lower level of contamination were in Daghara District . The results of the present study showed an increase in concentrations of nickel and mercury in March month . It could be concluded that high concentration of studied heavy metals in Al-Hamza District may be due to getting rid of the residues of industrial activities in Al-Diwania river without treatment, while in the other locations may be due to using sewage water for agricultural irrigation .